The Reality of Academic Guidance at the Algerian University - Laghouat University as a Model - - Mohamed BOUFATAH; Amel RIGHI (Social Sciences Journal, 2021)
This study which is titled « the actuality of the academic advising in the Algerian university » and at exploring the difference between students in this subject according to specialty. To reach that, the study is based and divided into theoretical and practical study, the theoretical contains a chapter explores the problematic in form of questions as follows:What is the actuality of the academic advising in the Algerian university?Are there any differences in the academic advising extend to the specialty?- The sample of the study is composed of (54) students at Ammar thliji university laghouat.- The second chapter of the study deals with the academic advising in which there is the « literary review of the definition of the academic ».- In the third chapter deals with Algerian university in which the theoretical circle and to all what has the books and resources before.- However, the fourth and the fifth are for the practical and it’s contains.- To achieve these goals, a questionnaire was used as a measuring tool it is devoted to students of Amar tlidji university, after the exception and analysis of the data the results orbited was analyzed by pourcentage-taux.- This has revealed the results of the study after analyzing data of the following:- There were statistically significant differences in the actuality of the academic advising in the Algerian university to academic specialty.